(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
Cyber Security as an education discipline covers a variety of topics that can be challenging and complex for students who are new to the subject domain. With this in mind, it is crucial that new students are motivated by understanding both the technical aspects of computing and networking, and the real-world implications of compromising these systems. In this paper we approach this task to create an engaging outreach experience, on the concept of cyber-physical systems, using a Scalextric slot-car racetrack. In the activity, students seek to compromise the underlying computer system that is linked to the track and updates the scoreboard system, in order to inflate their own score and to sabotage their opponent. Our investigation with this technique shows high levels of engagement whilst providing an excellent platform for teaching basic concepts of enumeration, brute forcing, and privilege escalation. It also provokes discussion on how this activity relates to real-world cases of cyber-physical systems security in the sports domain and beyond.